Handbook of semiconductor wafer cleaning technology science, technology, and applications - Kern, Werner, 1925- (Noyes Publications, 1993)
Discusses semiconductor wafer cleaning and the scientific and technical disciplines associated directly or indirectly with this subject. Intended to serve as a handbook for practitioners and professionals in the field.
Keywords: Semiconductor wafers -- Cleaning.; elektronické knihy; electronic books